Legal Protection for Children as Victims of Human Trafficking (Study of Decision Number 98/Pid.Sus/2020/Pn.Kot) - Sihombing, Freean Gabriel; Anggusti, Martono; Gultom, Meli Hertati (PT FORMOSA CENDEKIA GLOBAL, 2025)
Criminal acts are a significant concern for the surrounding community and require swift and appropriate handling to overcome them. The crime of human trafficking is a form of denial of the fundamental human status as a legal subject. It also results in cases of humanism that certainly degrade the dignity of humans as social beings. Indonesian law has a complex framework in protecting children from all forms of exploitation and crime, including the Crime of Human Trafficking (TPPO). Within the Indonesian legal system, there are various regulations designed to protect children's rights and provide protection against crimes that threaten their safety. This study uses a normative legal method with a statute approach, a fact approach, and a case approach. Based on the problem in this study, which discusses the Implementation of Legislation in the Protection of Child Victims of Trafficking, the Judge's Consideration in Imposing Sentences in Decision Number 98/Pid.Sus/2020/PN.Kot. Further analysis is needed to understand the judge's considerations and the application of the principle of justice in the decision.